Euro-Atlantic Security in U.S.-EURussia Triangle and Trump Factor - M. M. Panyuzheva (Vestnik MGIMO-Universiteta)
The article discusses the security relations among the United States, the EU and Russia in the context of Donald Trump's populism, the change of Western political elites and the erosion of arms treaty regimes. The purpose of the article is to analyze the current state and identify the probable scenarios of relations in the triangle of the USA – the EU – Russia. The article explores the features of the Euro-Atlantic security system from 1990’s till the mid-2000’s; the concept of Euro-Atlantic security in 2008-2009; the US, the EU and Russia relations under Barak Obama and Donald Trump. As a result of a comprehensive analysis, the author comes to the following conclusions: 1) the concept of Euro-Atlantic security is still relevant. Since the NATO based security arrangements are not stabile, security interaction among the USA, the EU and Russia is growing in importance. 2) European leaders seem to be moving towards building a new security architecture and a more balanced dialogue with Russia. The EU remains the main economic partner of the Russian Federation. 3) Trump's “transactional” approach has prompted Europeans to strengthen its defense identity and seek a compromise with Russia. 4) In a multipolar world, the Euro-Atlantic regional security is no longer closed to transatlantic ties. It is important to rethink the concept towards cooperation with non-regional countries. 5) The complex game of engagement and deterrence is likely to continue in relations between Russia and the West. The more uncertain the transatlantic relations become, the more the EU and the US need Russia.The author declares absence of conflict of interests.